
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.




\(A=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\sqrt{\frac{\left(x^4+x^2y^2\right)^2+\left(y^4+x^2y^2\right)^2+x^4y^4}{\left(x^2+y^2\right)^2}}}\)
\(=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\sqrt{\frac{\left(x^4+x^2y^2\right)^2+2x^4y^4+2x^2y^6+y^8}{\left(x^2+y^2\right)^2}}}\)
\(=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\sqrt{\frac{\left(x^4+x^2y^2\right)^2+2\left(x^4+x^2y^2\right)y^4+y^8}{\left(x^2+y^2\right)^2}}}\)
\(=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\sqrt{\frac{\left(x^4+x^2y^2+y^4\right)^2}{\left(x^2+y^2\right)^2}}}\)
\(=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\frac{x^4+x^2y^2+y^4}{x^2+y^2}}\)
\(=\sqrt{\frac{x^2y^2}{\left(x+y\right)^2}+\frac{x^4+2x^2y^2+y^4}{x^2+y^2}}=\sqrt{\frac{x^2y^2}{\left(x+y\right)^2}+\frac{\left(x^2+y^2\right)^2}{x^2+y^2}}\)
\(=\sqrt{\frac{x^2y^2}{\left(x+y\right)^2}+x^2+y^2}=\sqrt{\frac{\left(x^2+xy\right)^2+\left(y^2+xy\right)^2+x^2y^2}{\left(x+y\right)^2}}\)
\(=\sqrt{\frac{\left(x^2+xy\right)^2+2x^2y^2+2xy^3+y^4}{\left(x+y\right)^2}}=\sqrt{\frac{\left(x^2+xy\right)^2+2\left(x^2+xy\right)y^2+y^4}{\left(x+y\right)^2}}\)
\(=\sqrt{\frac{\left(x^2+xy+y^2\right)^2}{\left(x+y\right)^2}}=\frac{x^2+xy+y^2}{x+y}\)

Ta có: \(x^4+y^4+\frac{x^4y^4}{\left(x^2+y^2\right)^2}\)
\(=\left(x^4+2x^2y^2+y^4\right)-2x^2y^2+\frac{x^4y^4}{\left(x^2+y^2\right)}\)
\(=\left(x^2+y^2\right)^2-2x^2y^2+\left(\frac{x^2y^2}{x^2+y^2}\right)^2\)
\(=\left(x^2+y^2-\frac{x^2y^2}{x^2+y^2}\right)^2\)
Thay vào ta tính được:
\(P=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+\sqrt{\left(x^2+y^2-\frac{x^2y^2}{x^2+y^2}\right)^2}}\)
Mà \(x^2+y^2-\frac{x^2y^2}{x^2+y^2}=\frac{\left(x^2+y^2\right)^2-x^2y^2}{x^2+y^2}=\frac{x^4+x^2y^2+y^4}{x^2+y^2}>0\left(\forall x,y\right)\)
Khi đó:
\(P=\sqrt{\frac{x^2y^2}{x^2+y^2}+\frac{x^2y^2}{\left(x+y\right)^2}+x^2+y^2-\frac{x^2y^2}{x^2+y^2}}\)
\(P=\sqrt{x^2+y^2+\frac{x^2y^2}{\left(x+y\right)^2}}\)
\(P=\sqrt{\left(x^2+2xy+y^2\right)-2xy+\frac{x^2y^2}{\left(x+y\right)^2}}\)
\(P=\sqrt{\left(x+y\right)^2-2xy+\left(\frac{xy}{x+y}\right)^2}\)
\(P=\sqrt{\left(x+y-\frac{xy}{x+y}\right)^2}\)
\(P=\left|x+y-\frac{xy}{x+y}\right|=\left|\frac{x^2+xy+y^2}{x+y}\right|=\frac{x^2+xy+y^2}{x+y}\)
Vậy \(P=\frac{x^2+xy+y^2}{x+y}\)